(untitled) (Advances in Systems Science and Applications, 2021)
The strategic control of the purchase price for high-tech products and market competition is considered. For this purpose, a new bilateral oligopoly market model is proposed. The new model allows determining the purchase prices for high-tech products under the competition of suppliers with flexible production capacities. Parametric calculations of the purchase prices, the number of competing suppliers and their production capacities are performed depending on the unit price offered by the monopsonist customer. The purchase prices offered by the customers to guarantee the competitiveness of the market are determined. The customers’ optimal pricing policy that will reduce the purchasing costs and/or ensure the existence of competing suppliers in the long run is identified. A possible price reduction for high-tech products when applying this policy is calculated. The ranges of some characteristic market parameters (the capital-output ratio, the rates of order execution and order flow, and the number of potential order sources) for which this policy is efficient are determined.